2019
DOI: 10.3389/fmicb.2019.02832
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microbiota Across Developmental Stages of Aedes koreicus, an Invasive Mosquito Vector in Europe: Indications for Microbiota-Based Control Strategies

Abstract: Since it has been understood that gut microbiota of vector mosquitoes can influence their vector competence, efforts have been undertaken to develop new control strategies based on host microbiota manipulation, and aimed at suppressing the vector population or replacing it with a less competent one. For the proper design of such control strategies it is necessary to know the microbiota composition of the target vector species, how it is acquired, and how it changes throughout the host's life cycle. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 102 publications
5
33
0
Order By: Relevance
“…About 36% of the bacterial ASVs in the mosquito Aedes koreicus were shared between the larva and the pupa, and 24% of those observed in the pupa were found in the adult. These changes were explained as the renewal of the intestinal epithelial layers that occurs during the mosquito metamorphosis development (Alfano et al, 2019). In our study, 13.1% of the ASVs were shared between the egg masses and the larvae.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…About 36% of the bacterial ASVs in the mosquito Aedes koreicus were shared between the larva and the pupa, and 24% of those observed in the pupa were found in the adult. These changes were explained as the renewal of the intestinal epithelial layers that occurs during the mosquito metamorphosis development (Alfano et al, 2019). In our study, 13.1% of the ASVs were shared between the egg masses and the larvae.…”
Section: Discussionmentioning
confidence: 53%
“…It was thought that metamorphosis that occurs in mosquitoes eliminate most of the microbial communities; however, evidence of bacteria that were transmitted from one developmental stage of the host to its subsequent stage (transstadial transmission), suggested that bacterial clearance is not complete during life development (Alfano et al, 2019). We found that as the insect develops, it transfers bacterial ASVs to the next level.…”
Section: Discussionmentioning
confidence: 57%
“…Higher ASVs richness in water than in mosquito samples has been already described in Aedes spp. ( Dada et al, 2014 ; Dickson et al, 2017 ; Wang et al, 2018 ; Alfano et al, 2019 ). Among the bacterial genera present in the breeding site water and acquired by both CR and FO larvae, it is worth mentioning Chryseobacterium , which is known to localize in the larval gut (see Scolari et al, 2019 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, larval and pupal samples from Ae. koreicus were found to be dominated by this bacterial family ( Alfano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota, which can influence mosquitoes' vector competence, has recently been studied in Ae. koreicus to find potential bacterial candidates that could be used in control strategies against this mosquito vector and its pathogens [19].…”
Section: Introductionmentioning
confidence: 99%